Glaucoma Secondary to Uveitis in Children in a Tertiary Care Referral Center. (3rd April 2019) - Gautam Seth, Natasha; Yangzes, Sonam; Thattaruthody, Faisal; Singh, Ramandeep; Bansal, Reema; Raj, Srishti; Kaushik, Sushmita; Gupta, Vishali; Pandav, Surinder Singh; Ram, Jagat; Gupta, Amod
ABSTRACT: Purpose : To study outcome of secondary glaucoma in pediatric uveitis patients. Methods: Retrospective analysis of records of uveitis patients ≤16 years. Results : Of 182 pediatric uveitis patients, secondary glaucoma was seen in 48 patients (75 eyes, 26.23%) with female preponderance (F:M-29:19) . JIA was the most common etiology (35.71%). BCVA of ≥20/40 was seen in 22 eyes at presentation and in 38 eyes at final follow up (p<0.001). Twenty eight children (66.67%) received systemic antiglaucoma therapy while 17 children (21 eyes) required surgery (60.71%). Logistic regression showed pseudophakia could predict the higher use of oral antiglaucoma medication (p=0.03) while anatomical site of involvement was predictive of higher chances of surgery (p=0.003). Overall success was seen in 82.10% and 71.64% using IOP limit of 21 and 18 mmHg respectively at mean follow-up of 3.9 years. Conclusion : Pediatric uveitic glaucoma though require multitude of therapies, can be managed effectively with appropriate therapy.